Optoelectronic packaging - Mickelson, Alan R.; Basavanhally, Nagesh R.; Lee, Yung-Cheng (Wiley series in microwave and optical engineering, 1997)
The rapidly expanding field of packaging for optoelectronic devices challenges electrical engineers with a host of complex and daunting problems. The increasing intricacy of assemblage compounds the thorny interconnection issues associated with electronic packaging-how to assemble an array with many elements efficiently while maintaining thermal tolerance and simultaneously overcoming the ensuing modulation problems that generate electrical noise. Adding to these problems has been the absence, until now, of a single authoritative reference on the subject.